Peran Kelompok Relawan Orang Muda Ganjar (OMG) Jawa Tengah Sebagai Modal Sosial dalam Rivalitas Politik 2024 - Naufal Hanan Syahbana; Kuncoro Bayu Prasetyo (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
The year 2024 is considered a significant moment in Indonesia's democratic process, marked by the Presidential Election on February 14, 2024. One of the key factors in garnering support is social capital. The participation of young people has become a focal point in this phenomenon, highlighted by the presence of young political volunteers known as Orang Muda Ganjar (OMG). The purpose of this research is to explain the participation of OMG volunteers in Central Java in the 2024 Presidential Election through the lens of social capital. The research method used in this study is a qualitative approach, with data collection techniques including in-depth interviews, observation, and documentation. This study fills the gap in previous research, which has predominantly focused on the role of formal political parties while paying less attention to the contributions of volunteer groups as non-formal actors in politics. Based on the data, the findings show that friendships in academic environments are one of the reasons volunteers join and employ soft campaign strategies to reach out to young people by leveraging social capital. The most significant form of social capital contributing to garnering support is social networking, which utilizes existing relationships within student organizations. These social networks act as social capital in mobilizing support, which includes facilitating communication and coordination, building trust and solidarity, expanding outreach, and optimizing available resources. The researcher recommends further studies to explore the dynamics of social capital in various political contexts outside Central Java with different characteristics, as this could serve as a foundation for subsequent comparative studies.